Pembinaan Narapidana Penyalahgunaan Narkotika di Lembaga Pemasyarakatan Narkotika Klas II A Sungguminasa - Salmiah, Salmiah; Tahir, Heri (Phinisi Integration Review, 2021)
The study aims to discover: (1) the guidance model of narcotics convicts at Penitentiary of Class II A in Sungguminasa; (2) the implementation of guidance model for fostering narcotics convicts in Penitentiary of Class II A in Sungguminasa; and (3) the determinant factors in guiding the narcotics convicts in Penitentiary of Class II A in Sungguminasa. The study uses qualitative research with a descriptive approach. Based on the source, the types of data used are primary and secondary data. The primary data were obtained through interview with narcotics abuse convicts and the officers of Penitentiary of Class II A in Sungguminasa as well as documentation and observation. While the secondary data were obtained from various literatures such as books, laws, and other related sources. Data process and data presentation were conducted descriptively. The results of the study reveal that: (1) there are two guidance models in Narcotics Penitentiary of Class II A in Sungguminasa, namely the personality development model and independence development model or work hard, (2) the implementation of guidance model at Narcotics Penitentiary of Class II A in Sungguminasa has been conducted such as personality development and independence development, (3) the determinant factors in fostering narcotics convicts at Narcotics Penitentiary of Class II A in Sungguminasa are (a) the supporting factors, namely convicts participation in the process of guidance implementation at Narcotics Penitentiary of Class II A and the officers’ enthusiasm in providing such guidance so all programs can be conducted and (b) the inhibiting factors, namely inadequate and unbalanced facilities and infrastructure between the number of convicts and the number of officers at Narcotics Penitentiary of Class II A in Sungguminasa.